Impact of Climate Change on Livestock Production - Koirala, A.; Bhandari, P. (Nepalese Veterinary Journal, 2019)
Climate change is one of the global challenges of this century. There is increase in large number of climate related events. Livestock sector has also been affected by changing climate due to which there is increased loss of livestock assets and several other indirect losses. Some of the effects of climate change in livestock include thermal and cold stress, increased diseases incidences and decrease in the feed, fodder and water availability. This results in decreased animal production and productivity. he paper mainly reviews the impacts of climate change on livestock production.